PROFILE OF ENVIRONMENTAL LITERACY STUDENTS OF SMPN 3 TELUK KERAMAT - M. Miftahuddin; Fenny Roshayanti; Joko Siswanto (CV. ADIBA AISHA AMIRA, 2022)
The aim of this research is to find out and explain the environmental literacy profile of SMPN 3 Teluk Keramat students. This research method is a quantitative descriptive method. The population and sample of this study were class VII students of SMPN 3 Teluk Keramat with a sample of 68 people. The collection of students' environmental literacy data in this study used the standard Middle School Environmental Literacy Survey (MSELS) assessment. Data collection techniques used in this study include interview methods and test methods. Data analysis and data interpretation in this assessment are data reduction, categorization, synthesis, and developing working hypotheses. The results of the study showed that the environmental literacy of junior high school students had an average value of 49.95%, namely the sufficient criterion. The results of the study based on environmental literacy indicators obtained different average values, namely ecological knowledge of 9.15% (sufficient criteria), cognitive skills of 4.23% (low criteria), environmental awareness of 80.11% (good criteria), and environmentally responsible behavior of 70.75% (good criteria).